2020
DOI: 10.1007/s00425-019-03330-z
|View full text |Cite
|
Sign up to set email alerts
|

Important roles of glycinebetaine in stabilizing the structure and function of the photosystem II complex under abiotic stresses

Abstract: Main conclusion The molecular and physiological mechanisms of glycinebetaine stabilizing photosystem II complex under abiotic stresses are discussed, helping to address food shortage problems threatening the survival of growing population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 119 publications
1
42
0
Order By: Relevance
“…In addition, it facilitates osmotic adjustment by reducing the internal osmotic potential that contributes to water stress tolerance in plant cells. It also stabilizes the PSII and RuBisCO complexes during photosynthesis under stress conditions (Holmström et al 2000;Huang et al 2020). These are some of the positive effects of the application of exogenous betaine glycine in plants that grow under the pressure of salinity or drought stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it facilitates osmotic adjustment by reducing the internal osmotic potential that contributes to water stress tolerance in plant cells. It also stabilizes the PSII and RuBisCO complexes during photosynthesis under stress conditions (Holmström et al 2000;Huang et al 2020). These are some of the positive effects of the application of exogenous betaine glycine in plants that grow under the pressure of salinity or drought stress.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies carried out by Sakamoto and Murata (2000) and Saxena et al (2019) indicated that osmoprotectant substances, such as glycine betaine, play an essential role in cell stabilization by balancing the structure of the protein quaternary and membrane structure against the adverse effects of salinity. Besides, it facilitates osmotic adjustment by lowering the internal osmotic potential, which contributes to the ability to tolerate water pressure, stabilizing the PSII and RuBisCO complexes in the process of photosynthesis under seizure conditions (Holmström et al 2000;Wang et al 2019;Huang et al 2020). The positive effects and exogenous application of glycine in plants grown under salinity stress conditions have been shown to protect plant cells (Demiral and Türkan 2004;Saxena et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…GB (N,N ,N -trimethylglycine) is an amphoteric quaternary ammonium compatible osmolyte that confers tolerance under environmental stress [96,97]. Its main beneficial effects are through osmotic adjustment and stabilisation of the photosystem II complex, amongst others [96,98]. Not all plants are able to accumulate GB under abiotic stress, although crops and cultivars that produce higher amounts of GB are usually more tolerant to abiotic stress [97].…”
Section: Glycine Betaine (Gb)mentioning
confidence: 99%
“…Cold stress is detrimental to plants as it directly affects the rate of nutrient and water uptake, which may lead to cell starvation, desiccation, and consequent death. Reduced metabolism, which occurs in cold tension, results in a photo-inhibition, inhibition of the activity of the photosystem II and destabilization of the phosphorus lipid bilayers thereby, affecting the normal architecture of cell membranes [44,114] [113]. Also, the application of such biostimulants having the ability to outcompete the ice-nucleating activity of microorganisms is becoming an effective method to overcome the losses caused by cold/frost damages [3].…”
Section: Cold Stressmentioning
confidence: 99%